Race Relations in Halifax, Nova Scotia, During the Mid-Victorian Quest for Reform - Sutherland, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1996)
AbstractThis paper explores the dynamics of race in Nova Scotia's capital city through the 1840s and early 1850s. Black Haligonians actively sought to escape a legacy of marginalisation through participation in the politics of reform, which involved a dual struggle against oligarchy in Nova Scotia and slavery in America. White society responded with a contradictory blend of accommodation and resistance. Eventually, segregation, rather than integration, prevailed, a result that reflected white prejudice more than black preference.